Osimertinib versus platinum-pemetrexed in patients with previously treated EGFR T790M advanced non-small cell lung cancer: An updated AURA3 trial-based cost-effectiveness analysis - Shi, Yin; Pei, Rui; Liu, Shao (Frontiers in Oncology, 2022)
Background: A recently overall survival (OS) analysis from the AURA3 trial indicated that osimertinib improves median OS versus platinum-pemetrexed for patients with previously treated epidermal growth factor receptor (EGFR) T790M advanced non-small cell lung cancer (NSCLC). Here, we assessed the cost-effectiveness of second-line osimertinib versus platinum-pemetrexed, from the perspectives of the United States payer and the Chinese health care system. Methods: A Markov model was constructed to compare the costs and health outcomes of osimertinib versus platinum-pemetrexed in second-line treatment of EGFR T790M advanced NSCLC. Life years (LYs), quality adjusted life years (QALYs), costs, and incremental cost-effectiveness ratios (ICERs) were calculated. One-way and probabilistic sensitivity analyses assessed the robustness of the model. Cost-effectiveness was examined in the intention-to-treat (ITT) population and central nervous system (CNS) metastases population. Results: In the United States, compared with platinum-pemetrexed, osimertinib yielded additional effectiveness of 0.43 QALYs and -0.12 QALYs, with incremental costs of $67,588 and $16,465 in the ITT population and CNS metastases population, respectively. The ICERs of osimertinib over platinum-pemetrexed were $159,126/QALY and $-130,830/QALY, respectively. The probability of osimertinib being cost-effective was 37% and 5.76%, respectively, at the willingness-to-pay (WTP) threshold of $150,000/QALY. In China, osimertinib showed incremental effectiveness of 0.34 QALYs and -0.14 QALYs, with incremental costs of $1,663 and $-505, resulting in ICERs of $4,950/QALY and $3,754/QALY in the ITT population and CNS metastases population, respectively. At the WTP threshold of $37,489/QALY, there was a 100% and 26% likelihood that osimertinib was cost-effective in the ITT population and CNS metastases population. Conclusion: In the United States, second-line osimertinib treatment for EGFR T790M advanced NSCLC is not cost-effective compared to platinum-pemetrexed under the current WTP threshold. When the osimertinib price reduces, the economic outcome may become favorable. In China, assuming a WTP threshold of $37,489/QALY, osimertinib is the dominant treatment strategy compared with platinum-pemetrexed in the ITT population and provides cost savings for CNS metastases patients.